Topological van der Waals Contact for Two-Dimensional Semiconductors - Ghods, Soheil; Lee, Hyunjin; Choi, Jun Hui; Moon, Ji Yun; Kim, Sein; Kim, Seung Il; Kwun, Hyung Jun; Josline, Mukkath Joseph; Kim, Chan Young; Hyun, Sang Hwa; Kim, Sang Won; Son, Seok Kyun; et al. (ACS Nano, 2024)
The relentless miniaturization inherent in complementary metal-oxide semiconductor technology has created challenges at the interface of two-dimensional (2D) materials and metal electrodes. These challenges, predominantly stemming from metal-induced gap states (MIGS) and Schottky barrier heights (SBHs), critically impede device performance. This work introduces an innovative implementation of damage-free Sb2Te3 topological van der Waals (T-vdW) contacts, representing an ultimate contact electrode for 2D materials. We successfully fabricate p-type and n-type transistors using monolayer and multilayer WSe2, achieving ultralow SBH (∼24 meV) and contact resistance (∼0.71 kΩ·μm). Simulations highlight the role of topological surface states in Sb2Te3, which effectively mitigate the MIGS effect, thereby significantly elevating device efficiency. Our experimental insights revealed the semiohmic behavior of Sb2Te3 T-vdW contacts, with an exceptional photoresponsivity of 716 A/W and rapid response times of approximately 60 μs. The findings presented herein herald topological contacts as a superior alternative to traditional metal contacts, potentially revolutionizing the performance of miniaturized electronic and optoelectronic devices.
Keywords: Antimony telluride; Complementary metal-oxide-semiconductor technologies; Metal-induced gap state; Miniaturisation; Schottky-barrier heights; Topological insulators; Two-dimensional materials; Two-dimensional semiconductors; Van der Waals contacts; Vdw contact; antimony telluride; contact resistance; optoelectronics; Schottky barrier height; topological insulators; vdW contact